Impact of gut hormone FGF-19 on type-2 diabetes and mitochondrial recovery in a prospective study of obese diabetic women undergoing bariatric surgery. Issue 1 (December 2017) - Martinez de la Escalera, Lucia; Kyrou, Ioannis; Vrbikova, Jana; Hainer, Voitech; Sramkova, Petra; Fried, Martin; Piya, Milan; Kumar, Sudhesh; Tripathi, Gyanendra; McTernan, Philip
Abstract Background The ileal-derived hormone, fibroblast growth factor 19 (FGF-19), may promote weight loss and facilitate type-2 diabetes mellitus remission in bariatric surgical patients. We investigated the effect of different bariatric procedures on circulating FGF-19 levels and the resulting impact on mitochondrial health in white adipose tissue (AT). Methods Obese and type-2 diabetic women (n = 39, BMI > 35 kg/m2 ) undergoing either biliopancreatic diversion (BPD), laparoscopic greater curvature plication (LGCP), or laparoscopic adjustable gastric banding (LAGB) participated in this ethics approved study. Anthropometry, biochemical, clinical data, serum, and AT biopsies were collected before and 6 months after surgery. Mitochondrial gene expression in adipose biopsies and serum FGF-19 levels were then assessed. Results All surgeries led to metabolic improvements with BPD producing the greatest benefits on weight loss (↓30%), HbA1c (↓28%), and cholesterol (↓25%) reduction, whilst LGCP resulted in similar HbA1c improvements (adjusted for BMI). Circulating FGF-19 increased in both BPD and LGCP (χ2 (2) = 8.088;P = 0.018), whilst, in LAGB, FGF-19 serum levels decreased (P = 0.028). Interestingly, circulating FGF-19 was inversely correlated with mitochondrial number in AT across all surgeries (n = 39). In contrast to LGCP and LAGB, mitochondrial number in BPD patients corresponded directly with changes in 12 of 14 mitochondrial genes assayed (P < 0.01). Conclusions Elevated serum FGF-19 levels post-surgery were associated with improved mitochondrial health in AT and overall diabetic remission. Changes in circulating FGF-19 levels were surgery-specific, with BPD producing the best metabolic outcomes among the study procedures (BPD > LGCP > LAGB), and highlighting mitochondria in AT as a potential target of FGF-19 during diabetes remission.